Clinical Differences between Men and Women with Psoriatic Arthritis: Relevance of the Analysis of Genes and Polymorphisms in the Major Histocompatibility Complex Region and of the Age at Onset of Psoriasis. (16th April 2013) - Queiro, Rubén; Tejón, Patricia; Coto, Pablo; Alonso, Sara; Alperi, Mercedes; Sarasqueta, Cristina; González, Segundo; Martínez-Borra, Jesús; López-Larrea, Carlos; Ballina, Javier
Abstract : It has been shown that males with spondyloarthritis tend to suffer from more severe spinal disease while females are more likely to have peripheral joint involvement. Nevertheless, gender-related differences have not been thoroughly explored in psoriatic arthritis (PsA). In PsA, males accumulate more peripheral and axial joint damage compared to women. However, it is not clear whether these findings are secondary to differences in occupational physical activity, hormonal changes, or other factors. The present study analyzed the differences in clinical expression of PsA between men and women. We have also evaluated the possible existence of gender-linked differences in the distribution of genes and polymorphisms within the major histocompatibility complex and whether patients' age at the onset of psoriasis established any differences in these aspects. Women suffered more polyarthritis, greater functional impairment, and a larger number of swollen joints during followup. We appreciated a differential expression of certain MHC genes according to gender and age at onset of psoriasis. Our results point to the need to include patient's age at the onset of psoriasis and gender as key stratification elements in future studies of genetic associations in PsA.